Impact of very wide antral pulmonary vein isolation on esophageal temperature changes during pulsed field ablation. (19th May 2022) - Kirstein, B; Heeger, C; Vogler, J; Eitel, C; Phan, L; Keelani, A; Feher, M; Traub, A; Samara, O; Kuck, K; Tilz, R
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Esophageal thermal injury (ETI) is a serious drawback of available energy sources for atrial fibrillation (AF) ablation, especially on the posterior left atrial (LA) wall. Pulsed field ablation (PFA) is a novel non-thermal energy source with promising safety advantages over existing methods due to its unique myocardial tissue specificity sparing the esophagus. Objective: To evaluate esophageal temperature changes during very wide antral pulmonary vein isolation (PVI) using the PFA system. Methods: Thirteen consecutive AF patients (62% with paroxysmal AF; age: 61 years; 70% male) underwent first-time PFA under deep sedation. Eight pulse trains (2kV/2.5 sec, bipolar, biphasic, 4x basket/flower configuration each) were delivered to each pulmonary vein (PV). Extra pulse trains in the flower configuration were added for very wide antral circumferential ablation (vWACA). Continuous intraluminal esophageal temperature (TESO) was monitored with an S-shaped esophageal temperature probe. Results: A median of 32 (IQR 32;32) and 8 (IQR 8;9) pulse trains for PVI and vWACA with a procedural time and catheter dwell time of 67 min (IQR 61-69) and 17 min (IQR 16-18) were applied. PFA with vWACA resulted in consecutive posterior LA wall isolation in 11/13 patients. Fluoroscopically, the esophagus coursed near the right PVs in 2/13, left PVs in 8/13 and mid-posterior wall position in 3/13 patients. Maximum TESO increase from baseline was 0.8 ±0.9 °C. However, no clinically relevant TESO changes occurred (Table 1). On short-term, all patients remained asymptomatic for sore throat, cough, or other symptoms potentially related to ETI. No esophago-duodenoscopy was necessary. Conclusion: PFA of the PVs and lesion extension to the posterior LA wall demonstrated clinically non-significant TESO changes and has the potential to eliminate the risk of a thermal damage to the esophagus.